Radiological Assessment of Vascular access in Haemodialysis Patients. Issue 7 (May 2014) - Kamper, Lars; Frahnert, Michael; Grebe, Scott-Oliver; Haage, Patrick
Clinical examination is still the most important diagnostic tool and duplex ultrasonography is the imaging method of first choice. Radiological assessment of vascular access for haemodialysis includes preoperative analysis of vessel anatomy and postoperative surveillance for access maturation as well as diagnosis in vascular access insufficiency. Compared to ultrasonography digital subtraction angiography is superior for the evaluation of the central veins and allows diagnosis and treatment in one session. Computed tomography should only be used in patients with inconclusive ultrasonography results, for example, for the assessment of the central veins and visualization of the vascular tree. Gadolinium-enhanced magnetic resonance imaging is no longer recommended in dialysis patients, because it may trigger nephrogenic systemic fibrosis. In patients with a history of previous central venous catheters additional preoperative imaging of the central veins should be performed. In this article we review the different radiological imaging methods for preoperative assessment and suspected vascular access dysfunction.